First isolation and identification of Brucella microti in sheep and goats: new insights and implications for veterinary medicine - Freddi, L.; Djokic, V.; Dremeau, A.; Ribeiro, M.; Berthaud, M.; Bennasar, F.; Pailhous, C.; Lanterne, A.; Ferreira Vicente, A.; Ponsart, C. (Frontiers in Microbiology, 2025)
Many species from the genus Brucella are causative agents of the bacterial zoonosis brucellosis. Until recently, it was generally believed that these bacteria exhibit strict host specificity; however, recent findings suggest otherwise. Brucella microti is an atypical Brucella species, no threat to humans, with a broad host spectrum, primarily found in wildlife and rodents, and is the only Brucella species isolated from soil, aquatic environments, and frogs, suggesting its environmental persistence and adaptability to diverse ecological niches. Despite its environmental resilience and wide host range, B. microti has not been detected in domestic animals. This study, for the first time, shows the ability of B. microti to infect domestic small ruminants. During the 2024 prophylaxis campaigns across three farms in two French departments, two sheep and one goat tested positive on classical serological tests for brucellosis. Following bacteriological isolation, HRM-PCR and classical biotyping methods classified the strains as B. microti, rather than the expected zoonotic Brucella spp. (B. abortus, B. suis, and B. melitensis). Hybrid whole-genome sequencing, whole genome single nucleotide polymorphism (wgSNP), and multiple Loci variable-number tandem repeat analysis (MLVA) revealed that the three isolates were genetically closer to the reference B. microti CCM4915 strains, isolated in Central Europe, than previously detected French strains from farmed frogs. The infection of small ruminants by B. microti is even more unusual, as no strain-specific antimicrobial resistance or virulence genes were identified. These findings underscore the need for new diagnostic tools that can identify Brucellae on the species level for proper management and monitoring, particularly in regions with epizootic risks. Further research is essential to clarify the role of B. microti in animal health and risks for public health.